Emission Characterization and Health Risk Assessment of Volatile Organic Compounds from Automotive Painting in Thailand - Kultan, Vanitchaya; Thepanondh, Sarawut; Keawboonchu, Jutarat; Pinthong, Nattaporn; Malakan, Wissawa (UI Scholars Hub, 2025)
The automotive industry is a significant source of volatile organic compound (VOC) emissions, particularly from solvent-based painting processes. This study evaluated VOC characteristics and distribution to assess associated health risks for workers and communities at varying distances from automotive painting facilities in Thailand, focusing on stacks and wastewater treatment plants that handle solvent-containing wastewater. The findings revealed aromatic compounds were predominant (66% of the total emissions), followed by oxygenated VOCs (26%). The stacks mainly emitted aromatics such as toluene and ethylbenzene, whereas the wastewater released oxygenated VOCs, particularly methyl isobutyl ketone and methyl ethyl ketone. The exposure concentrations in each area were primarily influenced by wind direction, with higher levels observed by downwind. The hazard index for areas was less than 1, indicating safe noncarcinogenic risk levels. The lifetime cancer risk showed that ethylbenzene posed a probable risk in all areas (maximum 8.15 × 10⁻⁶ μg/m³), whereas 1,2-dichloroethane exhibited a probable risk within 200 meters of the facility (maximum 4.13 × 10⁻⁵ μg/m³). This study supports the development of comprehensive emission standards covering health-related compounds and guides residential planning to avoid potential health impacts.